(untitled) - Packer, James Innell; (1926-2020) (U.S.A, 1996)
This book is a poignant study of these very truths for Christians who are seeking to deepen their knowledge of God with small, daily doses of solid insight and on-target application. Suited for both personal and group use--with reflections at the end of each day's reading--Life in the Spirit encourages you to delve into the Scriptures as you learn about the specific work of the Holy Spirit. These 30 daily devotionals from one of Christianity's most respected names are a great starting point to inspire and instruct you in living a Spirit-filled life. As J.I. Packer suggests, `Use them as a springboard or trampoline before the Lord. Bounce on them, bounce off them, and see how high your heavenly Father enables you to go.`
Keywords: Holy Spirit -- Prayers and devotions -- English